Integrating Classical Qur’anic Exegesis and Modern Physiognomy: A Hermeneutical Analysis of Human Nonverbal Signals in Mafatih al-Ghaib - Hakim, Abdullah Ghafur; Bakar, Abu; Ameen, Nouval Fawzy (Universitas Muhammadiyah Surakarta, 2025)
This research delves into the idea of physiognomy as a means of interpreting human nonverbal cues within the context of the Qur'an and Fakhruddin al-Razi's commentary in Mafātihul Ghaib. Traditionally considered a pseudo-science, physiognomy is reimagined here as a link between the physical and spiritual aspects of human expression. The study addresses a gap in prior research, which often confines nonverbal analysis in the Qur'an to linguistic or semiotic aspects, neglecting psychological and spiritual dimensions. Employing a qualitative library research method, the study investigates nine Qur'anic verses that depict facial expressions, gestures, and bodily signals through al-Razi's hermeneutical perspective. The results indicate that al-Razi consistently views the human body as a communicative entity that expresses internal states-such as faith, arrogance, sorrow, and joy-through nonverbal cues that resonate with divine communication. By integrating al-Razi's interpretations with contemporary nonverbal communication theories, the study highlights an epistemological continuity between classical tafsir and cognitive science. This study aims to analyze how al-Razi interprets nonverbal human signals in the Qur'an and to connect his interpretation with modern cognitive science.